2010
DOI: 10.1007/s10528-009-9322-7
|View full text |Cite
|
Sign up to set email alerts
|

High-Altitude Adaptation of Yak Based on Genetic Variants and Activity of Lactate Dehydrogenase-1

Abstract: This study investigates the molecular mechanism by which yaks (Bos grunniens) adapt to hypoxia based on lactate dehydrogenase (LDH). Three LDH1 variants of the yak were revealed in tissue extracts by electrophoresis, including LDH1-F, LDH1-M, and LDH1-S. Kinetic analysis using purified LDH1 variants showed that the yak LDH1-M variant exhibited a similar K (m) (NADH) and the same mobility on a gel as bovine LDH1, and the LDH1-F variant showed significant differences in K (m) values for NADH or pyruvate from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…These results do not conform to the expectation that LDH activity would increase in cold temperatures, as well as low PO 2 conditions (Pasteur Effect) [31,35]. However, for better living in cold and hypoxia conditions, endemic animals inhabiting high altitudes have revealed a number of strategies to adjust the anaerobic metabolism level, including isozyme spectrum and specific expression of LDH-M and LDH-H [4244]. Furthermore, in accordance with our results, similar results were also predominantly found in some native animals at high altitude and hibernating animals [17,45].…”
Section: Discussionmentioning
confidence: 88%
“…These results do not conform to the expectation that LDH activity would increase in cold temperatures, as well as low PO 2 conditions (Pasteur Effect) [31,35]. However, for better living in cold and hypoxia conditions, endemic animals inhabiting high altitudes have revealed a number of strategies to adjust the anaerobic metabolism level, including isozyme spectrum and specific expression of LDH-M and LDH-H [4244]. Furthermore, in accordance with our results, similar results were also predominantly found in some native animals at high altitude and hibernating animals [17,45].…”
Section: Discussionmentioning
confidence: 88%
“…Kaaja and Are () found myocardial LDH activity was increased in rats exposed to hypobaric hypoxia (9.5% O 2 ) for 40 days. However high altitude yaks had lower LDH activity in heart muscle compared to those of low altitude (Kuang et al, ). Succinate dehydrogenase (SDH), bound to the inner mitochondrial membrane, is a key enzyme in aerobic energy production (Oyedotun and Lemire, ).…”
mentioning
confidence: 99%
“…We have previously identified two phenotypes of LDH1 in Maiwa yaks (a yak breed in China) by gene cloning [6], and purified three phenotypes of LDH1 in Jiulong yaks [9]. In this study we obtained three ldhb cDNA sequences, encoding H subunits, of the three LDH1 phenotypes of Jiulong yaks.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that yak LDH1-M phenotype exhibited a similar Km (NADH), and the same mobility on a gel as bovine LDH1, and the LDH1-F phenotype showed a significantly higher K m value for NADH and a lower K m value for pyruvate than yak LDH1-M and LDH1-S, as well as bovine LDH1 [9]. This suggests that LDH1-F is more suitable for catalyzing the conversion of pyruvate to lactate, and this will be of significance for energy production under hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation